Chemical Conditions Affecting Iron Oxides: Does the presence of phosphate within the structure of the iron oxides make them less reducible than synthetic pure ferrihydrite? - Shulman, Samantha (Université d'Ottawa | University of Ottawa, 2017)
The purpose of this study was to explore the redox stability of biogenic iron oxides and the implications for wastewater treatment. Specifically, we investigated if the presence of phosphate within the structure of ferrihydrite (an iron oxide) makes it less reducible (by iron reducing bacteria) than pure synthetic ferrihydrite. Experiments were conducted on four different synthetic ferrihydrite samples to determine the rates of ferric reduction by Shewanella putrefaciens CN32, a well-known iron reducing bacterium. The samples were: pure ferrihydrite, ferrihydrite and added alginate, ferrihydrite with 1 uM phosphate and a combination of the latter two. Our results showed that the addition of phosphate stabilized the ferrihydrite and slowed down the reduction process. Rates of reduction in mM Fe(II) per day were 0.0141 (ferrihydrite + alginate + PO4), 0.0423(ferrihydrite + PO4), 0.061(Ferrihydrite) and 0.0774 (ferrihydrite + alginate). This experiment confirms that sorbed phosphate onto ferrihydrite increases it redox stability, but its use as water treatment (to remove PO4 or other contaminants in waste waters), should take in account the potential for microbial reduction, especially if the iron oxide sludge is disposed of in landfills.